Country Partnership Framework for Republic of Botswana for the Period FY16-20 - World Bank Group (World Bank, Washington, DC, 2015)
This document details the scope and the main elements of the Country Partnership Framework (CPF) with the Republic of Botswana for FY16-20. The previous Country Partnership Strategy (CPS), considered by the Board on May 21, 2009 and completed in 2013 has built a solid foundation to design the new World Bank Group (WBG) program. The CPF supports the government’s ongoing National Development Plan (NDP10) that has recently been extended until 2017. It also reviews the new NDP11 now under preparation. The Systematic Country Diagnostic (SCD) was completed after Botswana’s General Elections in October 2014. The SCD drew on all available research and benefited greatly from the series of stakeholder consultations conducted in the country between March and September, 2014. The report was well received by the national authorities and sent for information to the Board on March 31, 2015. The SCD identified the following priority development challenges: (a) despite rapidly declining poverty, low job creation keeps inequality extremely high; (b) with the weakening of traditional growth drivers, a new growth model is needed that is jobs-intensive, export-oriented, and private sector-driven; (c) despite broad and well-intentioned investment, inclusion barriers remain; (d) sustainability is threatened as resource vulnerability challenges long-term growth and inclusion.